Optimizing the Role of Kamsel Unit Through the Police Goes to School Program in the Framework of Preventing Traffic Accidents in the Jurisdiction of Magelang Polres - Satriya, Sitanala (Advances in Police Science Research Journal, 2024)
Traffic accidents in Magelang Regency are dominated by students and students who do not have driving licenses. This is due to the limited public transportation, causing students to have to drive their motorized vehicles to go to and from school. And the lack of knowledge of parents and children about traffic rules so that parents allow their children to drive motorized vehicles. so the Kamsel Satlantas Unit needs to conduct more optimal traffic education. Theoretically, the results of writing can be useful for the development of science in the field of traffic and can be used as library material in the field of traffic. Theoretically, it is expected to be useful for the development of science in the field of traffic and can be used as library material in the field of traffic. Traffic accident prevention activities are expected to be input materials for policy formulation in traffic accident prevention. The research method used by researchers in this research report is qualitative with the presentation of descriptive data so that it is easy to understand. The implementation of Dikmas is then based on. Perpol No. 2 of 2021 Concerning Organizational Structure and Work Procedures at the Level of Resort Police and Sector Police (SOTK) The security and safety unit which is called the Kamsel Unit in the Traffic Unit Kamsel Satlantas Unit conducts Dikmas Then, including through the Police Goes To School program. The role of the Kamsel Unit in community education for students is limited to proposing and implementing community education according to the existing DIPA, while those who determine the amount of the budget are determined by higher-level police officials. The implementation of the Police Goes To School program has been carried out following the applicable laws and regulations but there is a need for efforts to increase the capacity of personnel through the Dikbngpes Dikmaslantas, FGDs led by Kanit Kamsel and parties who are experienced in the field of community education and then, write a letter to the local government regarding the proposal Dikmas Then is included in the local content curriculum in schools in Magelang district so that prevention of accidents is a joint responsibility of all policy stakeholders. With limited resources and infrastructure, the Kamsel Unit continues to carry out the activity program following what has been planned and other Dikmas activities that are incidental according to the orders of the leadership.